KNOWLEDGE OF FIRST AIR FOR DROWNING VICTIMS IN ISLAND AREAS - Indah Dwi Astuti; Rian Yuliyana; Elsa Gusrianti; Dinda Serli Hartati; Eka Putri Aruniska (Bajang Institute, 2021)
Berakit Village is one of the island areas in Teluk Sebong District, Bintan Regency, Riau Islands Province. Land cover on Berakit Island is mostly made up of mangroves (Directory of Small Islands of Indonesia, 2012). The high interaction of the village community with the sea has a high risk of drowning or near drowning. especially to the community and visitors who are traveling in the village. The purpose of this study was to describe the knowledge of first aid for drowning victims in the archipelago. This study used a descriptive method, The sample size in this study was 30 people. Based on the results of our observations through a questionnaire related to the description of knowledge about first aid for drowning victims in the Berakit Village community that the level of knowledge of the community was sufficient with a total of 19 people. This is due to several factors, one of which is the level of education. This is in accordance with the statement put forward by Nursalam (2011), that a person's knowledge can be influenced by the level of education and exposure to information. The higher a person's education, the easier it will be to receive information. It can be concluded that the majority of community knowledge in Berakit Village was sufficient, this is because the people in Berakit Village have received information about first aid for drowning victims